Dependence of the atmospheric muon rate on the sea water depth with first KM3NeT data - Lincetto, Massimiliano; Biagi, Simone; Coniglione, Rosa; Hofestädt, Jannik; Kulikovskiy, Vladimir; Melis, Karel W.; Samtleben, Dorothea F. E. (Proceedings of 36th International Cosmic Ray Conference — PoS(ICRC2019), 2019)
The first detection units of the KM3NeT/ORCA and KM3NeT/ARCA neutrino telescopes have been deployed at the French and Italian sites in the Mediterranean Sea. The first collected data have been crucial to assess the detector performance and to establish the calibration procedures. The low-level data streams of the deployed ARCA and ORCA detection units, containing raw information on hits in coincidence between PMTs for each Digital Optical Module, have been analysed. The study of coincidence rates has been exploited to evaluate the dependence of the atmospheric muon rate as a function of the sea depth, which is found to be in good agreement with model predictions.
CRIS-Team Scopus Importer:2024-12-16